-2(1+5a)=-(a+3)

Simple and best practice solution for -2(1+5a)=-(a+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(1+5a)=-(a+3) equation:


Simplifying
-2(1 + 5a) = -1(a + 3)
(1 * -2 + 5a * -2) = -1(a + 3)
(-2 + -10a) = -1(a + 3)

Reorder the terms:
-2 + -10a = -1(3 + a)
-2 + -10a = (3 * -1 + a * -1)
-2 + -10a = (-3 + -1a)

Solving
-2 + -10a = -3 + -1a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add 'a' to each side of the equation.
-2 + -10a + a = -3 + -1a + a

Combine like terms: -10a + a = -9a
-2 + -9a = -3 + -1a + a

Combine like terms: -1a + a = 0
-2 + -9a = -3 + 0
-2 + -9a = -3

Add '2' to each side of the equation.
-2 + 2 + -9a = -3 + 2

Combine like terms: -2 + 2 = 0
0 + -9a = -3 + 2
-9a = -3 + 2

Combine like terms: -3 + 2 = -1
-9a = -1

Divide each side by '-9'.
a = 0.1111111111

Simplifying
a = 0.1111111111

See similar equations:

| .6x-10=11 | | 3x+6x+10=12x-7-3x | | -3(-10-10u)=-2(-15-15u) | | -2x=-x-3 | | n+11=2h | | 3x+12=4x+10 | | -10-20h=-3(6h-10) | | 5(7k-8)=240 | | 3s+2t= | | -7(5j-20)=-17j-18j+18 | | c-4=2 | | X^2+4x+4x=55 | | 5x^2-10xy=0 | | x=2x-3y | | 4y+6y+15y=250 | | 4(9+8p)+p= | | 6/21-21/x4 | | 14t-9(15t-2)=8(-18t-15) | | 2(x+12)=4x-6 | | 8(x+1)=(x+9)(x+1) | | 7y+50=x | | 3-7y=21 | | 8h-12h=-16 | | 35+-4h=-1 | | 61=x^2 | | -3(t-3)+5t=8t-8 | | 3.91+14.2q=14.2q+3.91 | | 7c-12=-21 | | 5(x-4)=3x-16 | | p=-12000+2.5n | | 4y+3=5-2 | | 8x^3-18xy^2= |

Equations solver categories